Effects of beta indolacetic acid and calcium chloride in the rooting process in mulberry trees (Morus alba, L., var. Catânia 1) stakes in a green house, when planted in an inverted position - Rúbia, Antonio Castilho; Sarruge, José Renato; Abramides, Eduardo (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
In this work we present results of an experiment on the rooting process in Catânia 1 mulberry trees stakes, employing beta idolacetic acid and calcium chloride. The mentioned mulberry tree cultivar, which presents the highest leaves production, is propagated only by grafting, resulting from this that it can't be cultivated in the stump system (branches croping is done a the level of the soil); this does not occur regarding common cultivars, as their multiplication is normally done through stakes. Eight treatments were studied, as follows : a) The 1st one was the test. b) in the 2nd one we had the synthetic vegetable hormone, beta indolacetic acid (100 ppm). c) in the 3rd, 4th and 5th ones, we 've associated beta indolacetic acid to 2.5 ions mg Ca++ per 1,000 ml, 5.0 ions mg Ca++ per 1,000 ml, 10.0 ions mg Ca++ per 1,000 ml, respectively. d) 6th, 7th and 8th ones correspondend to the mentioned solutions of hydra ted calcium chloride. Results shown troughout statistical analysis were as follows: 1 - Thre was not a significative difference among treatments using beta indolacetic when associated or not to calcium chloride. 2 -Treatmensts in which beta indolacetic acid was used were superior to the other treatments on the average. 3 - Considering the conditions the experiment was carried over, we can conclude that the treatment with beta indolacetic acid associated to 10.0 mg Ca++ per 1,000 ml was superior to the other ones, followed by the reament in wich only beta indolacetic acid was employed. 4 - Variation coeficient was 19.08% - considere medium.